2015
DOI: 10.1016/j.jbiosc.2014.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Production of squalene by squalene synthases and their truncated mutants in Escherichia coli

Abstract: Squalene is a precursor of thousands of bioactive triterpenoids and also has industrial value as a lubricant, health-promoting agent, and/or drop-in biofuel. To establish an efficient Escherichia coli-based system for squalene production, we tested two different squalene synthases and their mutants in combination with precursor pathways. By co-expressing a chimeric mevalonate pathway with human or Thermosynechococcus squalene synthase, E. coli accumulated squalene up to 230 mg/L or 55 mg/g-DCW in flask culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 76 publications
1
56
0
1
Order By: Relevance
“…5A). To test these two possibilities, we first engineered Escherichia coli to produce high levels of squalene by introducing a plasmid that expresses the M. alcaliphilum squalene synthase (sqs) gene as well as a second plasmid that increases overall isoprenoid synthesis (40,41). This strain, also expressing M. alcaliphilum ths from a third plasmid, did not demethylate or otherwise modify squalene, nor did it produce tetrahymanol, indicating that Ths was not directly using squalene as a substrate (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5A). To test these two possibilities, we first engineered Escherichia coli to produce high levels of squalene by introducing a plasmid that expresses the M. alcaliphilum squalene synthase (sqs) gene as well as a second plasmid that increases overall isoprenoid synthesis (40,41). This strain, also expressing M. alcaliphilum ths from a third plasmid, did not demethylate or otherwise modify squalene, nor did it produce tetrahymanol, indicating that Ths was not directly using squalene as a substrate (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, previous study has demonstrated that native MEP pathway has a higher theoretical yield of terpenoid than MVA pathway in E. coli by genome-scale in silico modeling (Meng et al, 2011). Katabami et al (2015) used truncated squalene synthases from human (hsqs) in combination with MVA pathways to produce squalene up to 230 mg/L or 55 mg/g-DCW in flask culture, an approximately 55-fold increase as compared to E. coli harboring hsqs alone. In this study, in overexpression of key-enzymes genes dxs, idi and ispA of MEP pathway with double copy of SQS from Y. lipolytica in E. coli BL21(DE3), yield of squalene increased 71 folds, when compared with the strain that only harbor two copies of SQS.…”
Section: Discussionmentioning
confidence: 99%
“…Although further truncation was not investigated for MaSQS, it was predicted that three additional helixes and partial JK-loop removal in the C-terminal regions could lead to the inactivity of SQS due to the loss of NADPH binding (Fig. 2), which influence the dehydrosqualene synthase activity [17]. Moreover, the truncated MaSQSΔC17 was subjected to site-directed mutagenesis and the mutant mMaSQSΔC17 displayed an improved enzyme activity, indicating that the site E186 played a significant role in the catalytic ability.…”
Section: Discussionmentioning
confidence: 99%